Character Strengths – Stability, Change, and Relationships with Well-Being Changes - Gander, Fabian; Hofmann, Jennifer; Proyer, René T.; Ruch, Willibald (Applied Research in Quality of Life, 2020)
Character strengths are positively valued personality traits that are assumed to be stable across time and situations, but also malleable due to cultivation or deliberate intervention. Also, studies showed that character strengths are robustly related to well-being. Consequently, character strengths have often been used in interventions aimed at increasing well-being. However, the stability of character strengths and the longitudinal relationships with well-being are widely unexplored: First, previous reports on the stability of character strengths have mainly focused on one assessment instrument only and second, they did not consider other indicators of stability (and malleability) besides rank-order stability, (i.e., mean-level stability). In this longitudinal study, we assessed character strengths and well-being at two time points and examined the stability and malleability of character strengths and the convergence of changes in character strengths and well-being by means of correlation analyses. Two samples ( n 1 = 601, n 2 = 1162) completed different measures of character strengths and instruments for the assessment of well-being, ill-being, and health within up to three and a half years. Results showed that character strengths are stable over longer time periods (test-retest reliabilities ranging from r tt = .60–.83) and that relationships between changes in strengths and well-being are highly parallel to what has been reported in cross-sectional studies (strongest relationships for zest, hope, curiosity, and love). Furthermore, results suggest that some strengths, most predominantly humor, but also spirituality and prudence might be more amenable for change than others. These results might bear important information for selecting character strengths in interventions.